Educational-social role of Korean elementary school teachers in Russia in 1860s-1910s - Alina I. Khuzina, Young Cheol Ko, Ramil R. Khajrutdinov (Opción, 2019)
The aim of the study is to investigate the educational-social role of Korean elementary school teachers in Russia in 1860s-1910s via comparative qualitative research methods. As a result, most of the graduates of schools of Korean nationality were sent to study in the teachers’ seminary. In conclusion, the training of Koreans was necessary to increase the number of teachers in rural Korean schools and for the Orthodox mission, but it can be assumed a huge contribution to the achievement of this goal was made by Kazan Foreign Teacher’s Seminary.